2016
DOI: 10.7882/az.2016.031
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat selection varies by sex and age class in the endangered green and golden bell frog Litoria aurea

Abstract: Although amphibians are one of the most threatened animal groups, little published evidence exists on effective management programs. In order for conservation initiatives to be successful, an understanding of habitat use patterns is required to identify important environmental features. However, habitat use may differ between the different sexes and age classes due to different behavioural and resource requirements. For this study, we compared microhabitat use during the active breeding season among the sexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 86 publications
(114 reference statements)
1
7
0
Order By: Relevance
“…This result agrees with previous research from other regions: terrestrial habitat factors were found to be especially important in determining the suitability of breeding sites for Rana temporaria in Ireland (Marnell, 1998) and Sweden (Loman & Lardner, 2006). Previous studies have also found the importance of terrestrial habitats for amphibians within conservation programmes (Valdez et al, 2017) and for females of the green and golden bell frog Litoria aurea (Lesson, 1830) (Valdez et al, 2016). The terrestrial vegetation can determine the temperature of water, which plays an important role in amphibian breeding and development (Moore, 1939).…”
Section: Discussionsupporting
confidence: 92%
“…This result agrees with previous research from other regions: terrestrial habitat factors were found to be especially important in determining the suitability of breeding sites for Rana temporaria in Ireland (Marnell, 1998) and Sweden (Loman & Lardner, 2006). Previous studies have also found the importance of terrestrial habitats for amphibians within conservation programmes (Valdez et al, 2017) and for females of the green and golden bell frog Litoria aurea (Lesson, 1830) (Valdez et al, 2016). The terrestrial vegetation can determine the temperature of water, which plays an important role in amphibian breeding and development (Moore, 1939).…”
Section: Discussionsupporting
confidence: 92%
“…The observed sexual difference may be due to sampling bias. However, Valdez et al (2016) reported that only females actively select for terrestrial vegetation in the golden bell frog (Litoria aurea). In addition to protection from desiccation, terrestrial vegetation may provide opportunities for foraging (Pyke and White, 1996;Pyke and White, 2001) and shelters from predators (Valdez et al, 2016).…”
Section: Habitat Selectionmentioning
confidence: 99%
“…However, Valdez et al (2016) reported that only females actively select for terrestrial vegetation in the golden bell frog (Litoria aurea). In addition to protection from desiccation, terrestrial vegetation may provide opportunities for foraging (Pyke and White, 1996;Pyke and White, 2001) and shelters from predators (Valdez et al, 2016). The preference for terrestrial vegetation is a general trend of many amphibian species (e.g., Pyke and White, 2001;Valdez et al, 2016).…”
Section: Habitat Selectionmentioning
confidence: 99%
See 2 more Smart Citations